Patterning of Medial Consonants in English and Lithuanian - Strimaitienė, M. (Kalbotyra, 1979)
The present contrastive analysis of medial non-junctural (simple) consonant clusters in English and Lithuanian has disclosed the greatest similarity within the systems of two-member and three-member clusters. The similarity manifests itself both in patterning and individual clusters. The greatest difference is observed in fourmember clusters. Both English and Lithuanian non-junctural clusters sbare the same feature: more complex clusters imply the existence of more simple ones. This can be represented by the formula R(T)X ⊃ (T)X ⊃ X, where X is a consonant of any type or the clusters ST, SR, STR (in English and Lithuanian) and TR (in English); ⊃ – an implication symbol (“if then”). E. g., English distinctive /dis’tinktiv/, suspected /səs’pektid/ – Lithuanian añkštas, áukštas, vištà. Syllable boundaries in medial consonant clusters are established both in English and Lithuanian at the beginning of the maximum part of a medial cluster possible in a word initial position.